O ser-conhecido e o ser-não-conhecido em o Sofista de Platão - Zamboni, Luís Antonio (2023)
In this dissertation, Plato's work The Sophist is explored and the fundamental concept of being, implicit in the Platonic-epistemic-discursive ontology, is confronted in order to demonstrate the possibility of the false in the rhetorical discourses of the sophists. Thus, the central problem is the assumption of the resolution of an ontological problem, related to non-being, from an epistemic-discursive approach to reach the being-known and the being-not-known, in an intellectualizing ontology, in Parmenides and in Plato. To this end, we study the poem About the Nature by Parmenides and it is pointed out that the Parmenidian thesis is not fallacious, considering that the poem, by vetoing non-being, vetoes it in the scope of the universe of reals, “r”, and yet, Parmenides' thesis is not fallacious because, in the elevated instance Existence, beyond Space, the One, Forms and Mathematical Ideas, it is the same in itself, and resists, in rest, the contradiction of movement. In the present dissertation also: a narrative of the work is carried out; panoramic aspects of Platonic thought are pointed out; a discursive-epistemic-ontology is demonstrated to the possibility; it discusses the highest genres of being: movement, rest, being itself, same and other, making it possible to think about being-known and being-not-known that is being, so that in the universe of the Absolute, in the Existence, in Space, in the One and the Indeterminate Dyad, there is no non-being, because non-being is just another name given to being, in otherness. Still, the Himself-known and the Himself-not-known are presented. It leads from dualism to the one, in the Good and in the Unicity or in the Whole of God. It is involved in Divine omniscience, tangent to becoming, to the future. And the co-responsibility between creatures and Creator, ordered and Ordinator, is pointed out. For that, it is composed of seven chapters and uses the bibliographic review method.